Sweat rate and electrolyte concentration in swimmers, runners, and nonathletes - Henkin, S. D.; Sehl, P. L.; Meyer, F. (International Journal of Sports Physiology and Performance, 2010)
Because swimmers train in an aquatic environment, they probably do not need to sweat as much as runners who train on land and, therefore, should not develop the same magnitude of sweating adaptations. Purpose: To compare sweat rate and electrolyte concentration in swimmers, runners and nonathletes. Methods: Ten swimmers (22.9 ± 3.1 years old), 10 runners (25 ± 2.9 y) and 10 nonathletes (26.5 ± 2.2 y) cycled in the heat (32°C and 40% relative humidity) for 30 min at similar intensity relative to their maximal cycle test. Sweat volume was calculated from the difference of their body mass before and after cycling, since they were not allowed to drink. Sweat was collected from the scapula using absorbent patch placed on the skin that was cleaned with distilled water. After cycling, the patch was transferred to syringe and the sample was obtained when squeezing it to a tube. Concentration of sodium ([Na+]), chloride ([Cl-]) and potassium ([K+]) were analyzed using an ion selector analyzer. Results: The sweat volume, in liters, of swimmers (0.9 ± 0.3) was lower (P < .05) than that of runners (1.5 ± 0.2) and similar to that of nonathletes (0.6 ± 0.2). [Na+] and [Cl-], in mmol/L, of swimmers (65.4 ± 5.5 and 61.2 ± 81), and nonathletes (67.3 ± 8.5 and 58.3 ± 9.6) were higher (P < .05) than those of runners (45.2 ± 7.5 and 38.9 ± 8.3). [K+] was similar among groups. Conclusions: The lower sweat volume and higher sweat [Na+] and [Cl-] of swimmers, as compared with runners, indicate that training in the water does not cause the same magnitude of sweating adaptations.